Components of resistance to assess Black Sigatoka response in artificially inoculated Musa genotypes - Leiva Mora, Michel; Alvarado Capó, Yelenys; Acosta Suárez, Mayra; Cruz Martín, Mileidy; Roque, Berkis; Mena Méndez, Eilyn (Revista de Protección Vegetal, 2015)
ABSTRACT: Components of resistance were evaluated in seven Musa genotypes artificially inoculated with mycelia fragment suspensions of Mycosphaerella fijiensis Morelet (strain CCIBP-Pf80). Incubation period, number and area of necrotic lesions, infection index, area under the disease progress curve, asexual latent period, and number of spermogonia were evaluated in the genotype leaves to dissect the infective cycle of the fungus under greenhouse conditions. Incubation period in the inoculated leaves began at 14-21 days post infection, and significant differences were detected in the response of the different genotypes. Necrotic lesions were only observed in Grande naine, Pisang Awak, and significantly less in Pisang lilin. Grande naine reached the highest percentage of leaflet area with necrotic tissue, followed by Pisang Awak and Pisang lilin. Grande naine and Pisang Awak reached the greatest areas under the disease progress curves, while the lowest values were calculated in FHIA-18 and FHIA-25. The asexual latent period in Grande naine and Pisang Awak was significantly shorter (approximately 14 days) than in Pisang lilin. Greater numbers of spermogonia were observed in Grande naine and Pisang Awak, followed by Pisang lilin. Conidia were only detected in Grande naine, Pisang Awak and, in a significantly less number, in Pisang lilin. The different response observed of Musa spp. genotypes to the causal agent of Black Sigatoka indicated that the components of resistance used allowed the quantitative assessment of their reaction to this fungus. These results could improve or facilitate the efficiency and precision of the early evaluation process in banana and plantain breeding programs. Key words: early screening, inoculation, Mycosphaerella fijiensis, phytopathology, quantitative resistance. Componentes de la resistencia para cuantificar la respuesta a la Sigatoka Negra en genotipos de Musa inoculados artificialmente RESUMEN: Se evaluaron los componentes de la resistencia en genotipos de Musa inoculados artificialmente utilizando suspensiones miceliales de Mycosphaerella fijiensis Morelet (cepa CCIBP-Pf80). El periodo de incubación, número de lesiones necróticas, área de lesiones necróticas, índice de infección, área bajo la curva del progreso de la enfermedad, periodo de latencia asexual y número de Espermogonios se evaluaron en siete genotipos para analizar el ciclo infectivo de M. fijiensis en condiciones de invernadero. El período de incubación en todos los genotipos se enmarcó entre 14-21 días posteriores a la inoculación y se observaron diferencias significativas en la respuesta de los diferentes genotipos de Musa. El mayor número de lesiones necróticas se observó en el genotipo Grande naine en comparación con el Pisang Awak, y este a su vez, respecto al Pisang lilin. Los mayores valores del área bajo la curva del progreso de la enfermedad se observaron en los genotipos Grande naine y Pisang Awak, mientras los menores se calcularon en FHIA-18 y FHIA-25. Grande naine y Pisang Awak tuvieron una reducción significativa del periodo de latencia asexual (aproximadamente 14 días) respecto al Pisang lilin. El mayor número de espermogonio se observó en Grande naine y Pisang Awak, seguido del Pisang lilin. Los conidios solo se detectaron en hojas necrosadas de Grande naine y Pisang Awak, las cuales fueron significativamente superiores al Pisang lilin. Las diferencias observadas en la respuesta de los genotipos de Musa spp. frente al agente causal de la Sigatoka Negra, indicaron que los componentes de la resistencia utilizados permitieron evaluar cuantitativamente la reacción de Musa spp. frente al agente causal de BLSD. Estos resultados podrían facilitar una mayor eficiencia y precisión de la evaluación temprana de genotipos de bananos y plátanos en programas de mejoramiento genético. Palabras clave: fitopatología, inoculación, Mycosphaerella fijiensis, resistencia cuantitativa, selección temprana